Commissioning of a novel gantry-less proton therapy system - Feldman, Jon; Pryanichnikov, Alexander; Achkienasi, Alejandro; Polyansky, Ilya; Hillman, Yair; Raskin, Stas; Blumenfeld, Philip; Popovtzer, Aron; Marash, Michael (Frontiers in Oncology, 2024)
PurposeThe focus of this article is to describe the configuration, testing, and commissioning of a novel gantry-less synchrotron-based proton therapy (PT) facility.Materials and methodsThe described PT system delivers protons with a water equivalent range between 4 and 38 cm in 1800 energy layers. The fixed beam delivery permits a maximum field size of 28 × 30 cm2. The patient positioning and imaging system includes a six-degree-of-freedom robotic arm, a convertible patient chair, a vertical 4DCT, and an orthogonal 2D X-ray imaging system.ResultsThe spot positioning reproducibility was consistent within ±1 mm. The width (σ) of the beam profile at the isocenter was energy dependent and ranged from 2.8 mm to 7.7 mm. Absolute dose reproducibility was measured and deviations were found to be <0.62% for all possible beam scenarios. The built-in dose monitoring system was successfully tested for its ability to generate interlocks under specific conditions (beam spot deviation ≥2 mm, individual spot dose ≥10% or ≥0.25 Gy, spot energy deviation ≥0.5 MeV). The robot positioning exhibited a consistent reproducibility within ±1 mm. All tested scenarios achieved laser-free initial 3D/3D image-guided positioning within ±5 mm. Subsequent 2D/3D positioning showed an accuracy of ±1 mm. A single 2D/3D image registration event corrected positions in all cases. Results of gamma analysis (3%, 3 mm) demonstrated pass rates greater than 95% for head and neck, thorax, abdomen treatment plans.ConclusionsWe report on the performance of a novel single-room gantry-less PT system comprised of a compact synchrotron and an adjustable (from nearly horizontal to almost vertical) patient positioning system. The commissioning results show high accuracy and reproducibility of the main proton beam parameters and the patient positioning system. The new PT facility started patient treatments in March 2023, which were the first in Israel and the Middle Eastern region.